Konsep Dasar Dan Perkembangan Terbaru Dalam Organisasi Dan Arsitektur Komputer - Humendru, Dwi Cantika (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Computer architecture and organization are two fundamental aspects of computer systems design. While architecture refers to the structural design of computer components and their functional interrelations, organization focuses on the implementation and optimization of these components for efficient operation. This paper explores the basic concepts of computer architecture and organization, as well as the latest advancements in these fields. Additionally, the article explores various recent innovations, such as parallel architectures, cloud computing, and the use of more efficient processors and memory to enhance data processing capacity. Topics discussed include the evolution of quantum computing, heterogeneous computing, neuromorphic processors, chiplet-based architecture, artificial intelligence in computer design, and sustainable computing. These developments represent significant strides toward enhancing computing power, energy efficiency, and specialized application performance in modern systems. Understanding these concepts is crucial for professionals and researchers aiming to push the boundaries of computing technology. This research aims to provide a deeper understanding of the relationship between basic theory and the application of increasingly complex and diverse computer architecture technologies